Research and Analysis on Accessibility of Small populations to the Alternated and Undergraound Pedestrian Transitions on Automobile Roads - V. Enin, D. (International Journal of Engineering and Technology, 2018)
In the present article the results of field and sociological studies as well as analysis of accessibility of people with limited mobility of various categories of existing overhead and underground pedestrian crossings, equipped with ramps, on public roads are presented.Â Â